#TITLE_ALTERNATIVE# - RIYAN HARDIYANSYAH (NIM: 103 11 004), CECEP
Hyperluminous X-ray source (HLX) is a class of bright X-ray source with luminosity >1041 𝑒𝑟𝑔 𝑠−1. HLX is considered a distinct population which different from the majority of ultraluminous X-ray source (ULX) which has luminosity in the range of 1039−1041 𝑒𝑟𝑔 𝑠−1. This classification is needed because the presumption that its compact object and energy-generation mechanism are different from that of ULX. Most of ULX can be explained by stellar-mass black hole (<100 Mʘ) and energy-generation mechanism in the form of mass accretion with high mass accretion rate. However, this explanation is not appropriate to describe HLX due to the theoretical limitation on the increase of mass accretion rate. That is the increase of mass accretion rate does not always result in the increase of the luminosity. HLX cannot be explained with stellar-mass black hole scenario, but instead, should be explained with intermediate-mass black hole (IMBH) scenario. .....